Critical thinking skills: Error identifications on students’ with APOS theory - Khoerul Umam; Ardi Dwi Susandi (Institute of Advanced Engineering and Science, 2022)
Identifying students' errors in solving cases of critical thinking skills from two variables of linear equation (TVLE). This was a qualitative study using a descriptive exploratory approach. The participants of the study were first-year students of mathematics education. The method used in this research is a test, interview, and triangulation. The findings showed that the students have low critical thinking skills; therefore, they could not complete the task correctly. Based on the Action-Process-Object-Schema (APOS) theory, students' mistakes in completing math problems consist of four elements, namely: i) The errors in interpreting; ii) The errors in understanding the concept; iii) The error in the procedures; and iv) The error in technical things. The student's response in this study was in the theoretical of APOS, so that they could not reach a correct schema. The study results are expected to be beneficial in developing the activities in teaching TVLE, so that the students will make less errors in completing critical thinking skills problems in mathematics. Therefore, further study in developing a teaching model for mathematics teaching to improve students' critical thinking skills is highly recommended.